Therapeutic Effect of a Novel Phosphatidylinositol-3-Kinase δ Inhibitor in Experimental Epidermolysis Bullosa Acquisita - Koga, Hiroshi; Kasprick, Anika; López, Rosa; Aulí, Mariona; Pont, Mercè; Godessart, Núria; Zillikens, Detlef; Bieber, Katja; Ludwig, Ralf J.; Balagué, Cristina (Frontiers in Immunology, 2018)
Epidermolysis bullosa acquisita (EBA) is a rare, but prototypical, organ-specific autoimmune disease, characterized and caused by autoantibodies against type VII collagen (COL7). Mucocutaneous inflammation, blistering and scarring are the clinical hallmarks of the disease. Treatment of EBA is difficult and mainly relies on general immunosuppression. Hence, novel treatment options are urgently needed. The phosphatidylinositol-3-kinase (PI3K) pathway is a putative target for the treatment of inflammatory diseases, including EBA. We recently discovered LAS191954, an orally available, selective PI3Kd inhibitor. PI3Kd has been shown to be involved in B cell and neutrophil cellular functions. Both cell types critically contribute to EBA pathogenesis, rendering LAS191954 a potential drug candidate for EBA treatment. We here demonstrate that LAS191954, when administered chronically, dose-dependently improved the clinical phenotype of mice harboring widespread skin lesions secondary to immunization-induced EBA. Direct comparison with high-dose corticosteroid treatment indicated superiority of LAS191954. Interestingly, levels of circulating autoantibodies were unaltered in all groups, indicating a mode of action independent of the inhibition of B cell function. In line with this, LAS191954 also hindered disease progression in antibody transfer-induced EBA, where disease develops dependent on myeloid, but independent of B cells. We further show that, in vitro, LAS191954 dose-dependently impaired activation of human myeloid cells by relevant disease stimuli. Specifically, immune complex-mediated and C5a-mediated ROS release were inhibited in a PI3Kd-dependent manner. Accordingly, LAS191954 also modulated the dermal-epidermal separation induced in vitro by co-incubation of immune complexes with PMN, thus pointing to an important role of PI3Kd in EBA effector functions. Altogether these results suggest a new potential mechanism for the treatment of EBA and potentially also other autoimmune bullous diseases.